Pengaruh Kecerdasan Emosional, Kecerdasan Spritual Dan Kecerdasan Intelektual Terhadap Pemahaman Mata Kuliah Pengantar Akuntansi Dengan Perilaku Belajar Sebagai Variabel Moderasi Di PTN Dan PTS Kota Bengkulu: The Influence of Emotional Intelligence, Spiritual Intelligence and Intellectual Intelligence on the Understanding of Introduction to Accounting Courses with Learning Behavior as Moderating Variables in Bengkulu City State and Private Colleges - Riswandi, Pedi; Lakoni, Idham (Journal of Accounting Science, 2017)
This research is constituted to investigate the effect of emotional intelligence, spiritual intelligence and intellect to the understanding of introductory accounting courses to study behavior as a moderating variable. This research method is survey by questionnaire is a research taking samples of 78 students in Universities and Colleges as a means of collecting basic data. Test equipment used to test the hypothesis is logistic regression and then the test results be interpreted. This research is expected to contribute fundamental knowledge for Higher Education in order to improve the level of understanding of students of economic faculties. The results using multiple regression analysis showed emotional intelligence and spiritual intelligence significantly influence the level of understanding of introductory accounting courses and learning influence significant influence as a moderating variable.